Performance in a novel environment subject to ghost competition - Bisschop, Karen; Mortier, Frederik; Bonte, Dries; Rampal Etienne (bioRxiv, 2019)
A central tenet of the evolutionary theory of communities is that competition impacts evolutionary processes such as local adaptation. Species in a community exert a selection pressure on other species and may drive them to extinction. We know, however, very little about the influence of unsuccessful or ghost species on the evolutionary dynamics within the community. Here, we studied the long-term influence of a ghost competitor on the performance of a more successful species using experimental evolution. We transferred the spider mite Tetranychus urticae onto a novel host plant under initial presence or absence of a competing species, the congeneric mite T. ludeni. The latter species unintentionally went extinct soon after the start of the experiment, but we nevertheless completed the experiment and found that the initial density of this ghost competitor positively affected the performance (i.e. fecundity) of the more successful species. This effect on T. urticae even lasted for at least 25 generations. Our study supports the hypothesis that early experienced selection pressures can exert a persistent evolutionary signal on species′ performance in novel environments.